Analisis Interdependensi Neraca Transaksi Berjalan – Neraca Modal Indonesia Pendekatan Model Vector Autoregressive dan Vector Error Correction 1981.1 – 2002.3 - Akhmad Syakir Kurnia (Universitas Islam Indonesia, 2005)
This paper analyze interrelations between current account and capital account of Indonesia based on quarterly data from 1981.1 to 2002.3. Indonesias’ Current Account defi¬cit had been financed by huge capital inflows. A positive net capital inflow implies a higher stock of financial claims by the rest of the world against the resident and hence larger profit remittances and dividend and/or interest payments in the future.Johansen Cointegration test applied in this analysis shows that there is a cointe¬gration between current account and capital account with one cointegration equation. The result is consistence with Granger causality test, which shows that there is a bilateral cau¬sality between them. Through Bivariate Vector Autoregressive (VAR), it also could be seen that positive net capital inflows will cause deficit pressure on current account at first, third, fifth, and seventh quarter in the future (one-quarter break). Impulse Response Analysis also shows that positive net capital inflow will cause deficit pressure on current account one-quarter break after. But response of current account to the capital shock will not cause per¬manent impact on the current account. Current account will response to the capital shock till eleventh quarter after shock. After that, it will be back to its’ long term equilibrium. Through the analysis of variance decomposition, it could be seen that the response of current account to the shock is mostly caused by the shock of current account itself. Based on vector error correction model (VECM), there is short term and long term adjustment processes. The speed of adjustment of current account towards its long term equilibrium, shown by the coefficient of ECT is 36.05% per quarter, but that of capital ac¬count is faster, 109.9% per quarter (shorter than one quarter).This research concludes that there is interdependence between current account and capital account. Positive net capital inflows could be a major cause of current account defi¬cits in the future, so stabilizing of balance of payment has also come to include stabilizing of capital account.Keywords: Current Account, Capital Account, Balance of Payments, Vector Autoregressive (VAR), Impulse Response Analysis, Variance Decompositions, Cointegrations, Vector Error Correction Model (VECM).